The Database as Cultural Technique – Genealogy, Politics and Practices (KULT_online, 2013)
In the volume Sortieren, Sammeln, Suchen, Spielen. Die Datenbank als mediale Praxis, edited by Stefan Böhme, Rolf F. Nohr, and Serjoscha Wiemer, all 15 contributions investigate databases as a cultural technique, which obviously seems to be a constituent element of our current time. By focusing on the practices of arranging, collecting, searching, and gaming, the contributions give many examples in the name of identifying the multiple facets of databases, and conceptualize them by means of some important analyses like Lev Manovich's Database as Symbolic Form (1999) and Mark Poster's The Second Media Age (1995) in the field of media studies as media practice.